The Economic Burden of Different Multiple Sclerosis Courses: Analysis from Italian Administrative and Clinical Databases - Cortesi, Paolo Angelo; Cozzolino, Paolo; Capra, Ruggero; Cesana, Giancarlo; Mantovani, Lorenzo Giovanni (Farmeconomia. Health Economics and Therapeutic Pathways, 2020)
INTRODUCTION: Poor specific economic information are available for the different Multiple Sclerosis (MS) courses: relapsing remitting (RRMS), secondary progressive (SPMS) and primary progressive (PPMS). This study aims to fill this gap. METHODS: A cost of illness study was conducted. Clinical information of patients treated in a major MS Center located in Lombardy, in the period 2004-2010, were linked with administrative data of Lombardy Healthcare System. We assessed the mean cost per patient-year and its association with different MS characteristics. RESULTS: The study identified 869 patients (83.9% RRMS, 8.5% SPMS, 7.2% PPMS). RRMS reported the highest cost per patient-year with a mean of € 5,623 in Expanded Disability Status Scale (EDSS) 0-3, € 8,675 in EDSS 3.5-6.5, and € 7,451 in EDSS 7-9. The PPMS patients reported the lower annual mean cost per patient in all EDSS categories. The mul-tivariate analysis reported a significant association between cost per patient-year and EDSS categories, relapse and use of Disease Modifying Therapies but not to MS courses, age and sex. CONCLUSION: This study provides a complete picture of MS courses direct costs at the different disability levels. The results can help to better understand the burden of each MS courses and the cost-effectiveness of different interventions.